2018
DOI: 10.3389/fgene.2018.00261
|View full text |Cite
|
Sign up to set email alerts
|

Host and Viral Genetic Variation in HBV-Related Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the fifth most common cancer in men and the second leading cause of cancer deaths globally. The high prevalence of HCC is due in part to the high prevalence of chronic HBV infection and the high mortality rate is due to the lack of biomarkers for early detection and limited treatment options for late stage HCC. The observed individual variance in development of HCC is attributable to differences in HBV genotype and mutations, host predisposing germline genetic variations, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
116
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 122 publications
(120 citation statements)
references
References 128 publications
(275 reference statements)
3
116
0
1
Order By: Relevance
“…Based on KEGG pathways, we discovered that significant pathways were related to different cancers, indicating that these identified mutated genes might play critical roles in the development of multiple types of cancers. The mutated genes associated with Wnt signaling pathways and cell cycle pathways have been reported to facilitate the development of HCC . Consistent with published studies, based on WIKI pathways, we found that the pathways related to Wnt signaling and cell cycle were enriched by the identified mutated genes in HBV‐related HCC.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Based on KEGG pathways, we discovered that significant pathways were related to different cancers, indicating that these identified mutated genes might play critical roles in the development of multiple types of cancers. The mutated genes associated with Wnt signaling pathways and cell cycle pathways have been reported to facilitate the development of HCC . Consistent with published studies, based on WIKI pathways, we found that the pathways related to Wnt signaling and cell cycle were enriched by the identified mutated genes in HBV‐related HCC.…”
Section: Discussionsupporting
confidence: 90%
“…HBV infection could cause genomic instability, including mutation and epigenetic misregulation in genes, and multiple mechanisms are involved in gene mutation mediated by the virus. For example, HBV is capable of interfering with the function of mitotic regulatory proteins and mitotic spindle checkpoint proteins, which have the role of maintaining genomic integrity . The virus could integrate the viral genome into the host DNA to induce genetic alterations .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations